What is the first step in simplifying the expression (2 – 3 x 4 + 5) Question What is the first step in simplifying the expression (2 – 3 x 4 + 5) in progress 0 Math Gianna 2 hours 2021-09-13T03:17:17+00:00 2021-09-13T03:17:17+00:00 2 Answers 0

## Answers ( )

Answer: you multiply because of pendants

Step-by-step explanation:

P = parentheses

E = exponent

M = multiplication

D = division

A = addition

S = subtraction

Always follow the pemdas when it comes to an equation like that

Take a screenshot just to have it in mind

Multiplying -3 and 4 to get -12

The first step is multiplying -3 and 4

they are all in parentheses and usingbecausePEMDASP-Parentheses

E-exponents

M-multiply or D- division (whichever is first in the expression)

A-addition or S-subtraction (whichever is first in the expression)